2008
DOI: 10.1080/03079450802357019
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of cryptosporidiosis in a collection of Stone curlews (Burhinus oedicnemus) in Dubai

Abstract: We describe an outbreak of cryptosporidiosis in Stone curlews kept in a mixed-species rearing unit in Dubai. Cryptosporidium was the predominant intestinal pathogen detected, although microbiological investigations revealed a concurrent Salmonella infantis infection in two of the 29 Stone curlew chicks that died. Nineteen of 29 birds had catarrhal enteritis associated with histopathological findings of numerous Cryptosporidium developmental stages at the mucosal surface. Catarrhal enteritis was present without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 29 publications
0
20
0
3
Order By: Relevance
“…Three of the Cryptosporidium genotypes belonged to goose genotypes I (geese 1, 2, 3a, 6 and 8) and II (goose 9) and the duck genotype (goose 5) whereas the remaining two genotypes (geese 3b and 7) represented new Cryptosporidium genotypes; goose genotype III and IV respectively. Recently, C. parvum was confirmed by molecular analysis in an outbreak of intestinal cryptosporidiosis in Stone curlews kept in a mixed-species rearing unit in Dubai (Zylan et al, 2008), confirming the ability of C. parvum to infect avian hosts.…”
Section: Goose Genotypes I-ivmentioning
confidence: 82%
“…Three of the Cryptosporidium genotypes belonged to goose genotypes I (geese 1, 2, 3a, 6 and 8) and II (goose 9) and the duck genotype (goose 5) whereas the remaining two genotypes (geese 3b and 7) represented new Cryptosporidium genotypes; goose genotype III and IV respectively. Recently, C. parvum was confirmed by molecular analysis in an outbreak of intestinal cryptosporidiosis in Stone curlews kept in a mixed-species rearing unit in Dubai (Zylan et al, 2008), confirming the ability of C. parvum to infect avian hosts.…”
Section: Goose Genotypes I-ivmentioning
confidence: 82%
“…However, parasite colonization was found to be restricted to the respiratory tract, and low numbers of oocysts were produced. Cryptosporidium species that are more common among mammals are sporadically found in birds, either in association with clinical signs, such as C. parvum in the stone curlew (Burhinus oedicnemus) (ZYLAN et al, 2008), or asymptomatically in birds, as reported by Qi et al (2014) for ostriches with Cryptosporidium muris present in their feces.…”
Section: Proventriculusmentioning
confidence: 99%
“…1 Phylogenetic tree of the Cryptosporidium spp. isolated from exotic birds and those deposited in GenBank; bootstrap 1,000; Kimura two-parameter parvum in birds (Zylan et al 2008), and it is possible to experimentally infect birds with C. parvum (Lindsay et al 1986;Palkovic and Marousek 1989). Shedding of oocysts in feces of free-living birds has been reported (Graczyk et al 1998;Zhou et al 2004).…”
Section: Discussionmentioning
confidence: 98%